Empire of guns : the violent making of the industrial revolution - Satia, Priya (New York Penguin Press, 2018)
"We have long understood the Industrial Revolution as a triumphant story of innovation and technology. Empire of Guns, a rich and ambitious new book by award-winning historian Priya Satia, upends this conventional wisdom by placing war and Britain's prosperous gun trade at the heart of the Industrial Revolution and the state's imperial expansion. Satia brings to life this bustling industrial society with the story of a scandal: Samuel Galton of Birmingham, one of Britain's most prominent gunmakers, has been condemned by his fellow Quakers, who argue that his profession violates the society's pacifist principles. In his fervent self-defense, Galton argues that the state's heavy reliance on industry for all of its war needs means that every member of the British industrial economy is implicated in Britain's near-constant state of war"--
Includes bibliographical references (pages 417-507) and index.
Keywords: Galton, Samuel; Firearms industry and trade